A Pentagram Suture Technique for Closing Tumor Resection Sites in the Face. Issue 8 (August 2015) - Matsumine, Hajime; Takeuchi, Masaki; Mori, Satoko; Sakurai, Hiroyuki
Abstract : Background: Resection of facial skin tumors aims to remove the tumors completely and make the surgical scar unnoticeable as much as possible. By improving the purse string suture method, we developed a new pentagram suture technique that enables simple and safe suturing of small to large defects with early satisfactory esthetic outcomes. The surgical outcomes of a case series were examined in this report. Methods: As in drawing a unicursal star, 5 suture sites were marked at specific intervals around the defect area. A needle with 5-0 polydioxanone suture was passed from the subcutaneous tissue to the superficial dermal layer at one site and then from the superficial dermal layer to the subcutaneous layer at the next site, and the process was repeated until the pentagram was complete. When apposition was not tight enough, a couple of external stitches were added using 6-0 nylon suture. Results: In 13 patients (16 benign or malignant tumors; mean age, 51.1 years) with a mean tumor size of 10.1 ± 5.2 mm and postoperative skin defect diameter of 12.1 ± 8.2 mm, closure did not result in high tension on the suture, and there was reduced mechanical stress at the wound margin. Surgical outcomes were good esthetically at 6 months after surgery without keloid formation or scar contracture. None of the patients had postoperative pain, infection, or tumor recurrence. Conclusions: This simple alternative method for the closure of facial skin defects after skin tumor excision could be performed easily and provided satisfactory surgical outcomes.